PENGARUH PENGGUNAAN PREMIK YANG MENGANDUNG Zn ORGANIK DALAM RANSUM PUYUH PETELUR (Coturnix coturnix japonica) TERHADAP GROSS MARGIN PETERNAK - , BAGAS PRASETYO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was analyzed the difference gross margin based on the provide of feed with treatment control with using Zn organic and measuring the gross margin highest in some treatment granting feed with Zn organic. This research was started from November 2012 until February 2013. Two hundred eighty eight Japanese quail (Coturnix coturnix japonica) were randomly plotted within four treatment by four replication every treatment and consisted of eighteen bird each. The treatment were : P0 (contain Zn organic premix with content of 0 %), P1 (Zn organic of 1